Resistance of four mutant rice (Oryza sativa L.) Varieties to iron toxicity at Njala inland valley swamp ecology in southern Sierra Leone - Yankson, Dennis Philip Yaw; Kanu, Sheku Afred; Mansaray, Ibrahim; Bah, Alieu Mohamed (International Journal of Sustainable Agricultural Research, 2024)
Four lowland rice varieties were examined for tolerance to Fe toxicity using morphological traits. In 2021, at the Njala Agricultural Research Centre (NARC), we conducted a field trial at the Inland Valley Swamp (IVS) in Sierra Leone. The four rice varieties, Bina 8, 10, 17, and Early Mutant, were planted in a randomized complete block design with three replications. The variance analysis revealed significant differences in all four rice varieties' traits. Elemental analysis of plant stalk revealed that Early Mutants and Bina 17 had the lowest Fe2+ concentrations (0.4 mg/kg soil and 0.8 mg/kg soil, respectively). On the other hand, Bina 10 and Bina 8 had higher Fe2+ concentrations (3.5 mg/kg soil and 1.5 mg/kg soil, respectively). In contrast, Bina 8 and Bina 10 had higher Fe2+ concentration values in their roots and stalks, indicating a higher accumulation of Fe2+. Thus, these two varieties also had the highest yield, indicating they tolerate Fe toxicity. This finding implies that rice varieties' capacity to withstand Fe toxicity plays a crucial role in sustaining growth and yield in Fe-toxic environments. The study concludes that screening rice varieties for Fe toxicity tolerance is important, but further research is needed to understand the mechanisms underlying Fe toxicity tolerance in rice.